Estudo sobre a furação de compósito de resina epóxi reforçado com fibras de vidro - Paulo Eustaquio de Faria (2007)
The technological development has allowed the manufacture of sophisticated goods, leading to the pursuit of materials able to satisfactorily fulfill these requirements. Materials such as traditional metals, polymers and ceramics are still widely employed; however, theyhave been increasingly replaced by composite materials, which must be processed to the finished geometry and dimensions. This work is concerned with drilling of glass fibre reinforced epoxy resin using high speed steel and cemented tungsten carbide drills with distinct geometries and under various cutting parameters. In addition to the work material characterization, the experimental work involved measuring of feed force, tool wear, hole delamination, hole wall roughness, dimensional and circularity deviations and chip form. In general, the results indicated that feed rate, bundle thickness and drill geometry were the principal parameters affecting feed force. As far as the tool wear is concerned, the high speed steel drill showed severe wear after drilling 1000 holes, whereas the carbide drill presented negligible wear after producing 24000 holes. Abrasion was the principal wear mechanism observed and the use of coated carbide drill did represent any improvement in tool wear resistance and feed force. Delamination of the holes was affected by drill geometry and wear, i.e., the higher the cutting edge angle and the feed rate, the higher the delamination. Furthermore, the damage is accentuated when feed rate is reduced. The wall surface roughness increases with feed rate, however, it was less sensitive to changes in cutting speed. The dimensional (diameter) and circularity variations were strongly affected by tool wear. The quality of the hole wall generated by the tungsten carbide drill was superior to that produced by the high speed steel tool. Finally, thicker chips were generated when drilling at higher feed rates. Additionally, increasing tool wear resulted in chips in the powder form.